COMPARISON OF SALES EFFECTIVENESS OF BROMEN PRODUCTS ON DIGITAL MARKETING PLATFORMS BASED ON ADVERTISING EXPENSE - Ndorifah Ndorifah; Arief Nurdiannova Qurochman (Jurnal Ekonomi, 2023)
Sales of a product are currently mostly done online or throughdigital marketing platform.This study aims to determine Bromen product sales comparison at threedigital marketing platformsnamely Tiktok, Shopee, and Lazada based on advertising expenses, as well as the role of advertising expenses in selling Bromen products. PThis research uses ROAS as the basis for calculating sales compared to advertising expense on three digital marketing platforms (Tiktok, Shopee and Lazada). The comparative results of ROAS calculations on the three platforms show that there are significant differences in terms of the average and maximum ROAS values. On average, the highest ROAS at Shopee was 7.92, followed by ROAS at Lazada at 2.61, and finally ROAS at Tiktok Shop at 1.85. Likewise with the highest maximum ROAS value at Shopee of28.14, then at Lazada it was 8.07, and finally at Tiktok Shop it was 2.46. Meanwhile, in the relationship between variables, namely between variablesadvertising expensewith sales through the t test, F test, and the correlation and coefficient of determination, the result is that the t and F tests both conclude thatvariableadvertising expensevery influential on sales as evidenced by the level of Sig. on the t test and F <0.05. While the magnitude of influencevariableadvertising expenseto sales was 98.4%.